2023
DOI: 10.3390/robotics12050120
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Design of an Embodied Conversational Agent to Help Stroke Survivors Manage Their Recovery

Deborah Richards,
Paulo Sergio Miranda Maciel,
Heidi Janssen

Abstract: Whilst the use of digital interventions to assist patients with self-management involving embodied conversational agents (ECA) is emerging, the use of such agents to support stroke rehabilitation and recovery is rare. This iTakeCharge project takes inspiration from the evidence-based narrative style self-management intervention for stroke recovery, the ‘Take Charge’ intervention, which has been shown to contribute to significant improvements in disability and quality of life after stroke. We worked with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…While these studies have shown significant improvements in the desired outcome (i.e., adherence, health outcomes, attitudes and self-efficacy), we received negative feedback from users related to the lip-syncing animations, using terms such as freaky and creepy. In addition, Richards, Miranda Maciel and Janssen's [31] evaluation of a VA designed to help stroke survivors take charge of their recovery found that some stroke survivors, such as those with aphasia, were overwhelmed by the multiple audio and visual elements. In particular, in addition to the VA using audio to speak the dialogue, the dialogue was provided in text on the screen and the mouth of the avatar moved to match the audio (lip-syncing).…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…While these studies have shown significant improvements in the desired outcome (i.e., adherence, health outcomes, attitudes and self-efficacy), we received negative feedback from users related to the lip-syncing animations, using terms such as freaky and creepy. In addition, Richards, Miranda Maciel and Janssen's [31] evaluation of a VA designed to help stroke survivors take charge of their recovery found that some stroke survivors, such as those with aphasia, were overwhelmed by the multiple audio and visual elements. In particular, in addition to the VA using audio to speak the dialogue, the dialogue was provided in text on the screen and the mouth of the avatar moved to match the audio (lip-syncing).…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%